IMPROVING STUDENT’S ABILITY IN DESCRIBING THINGS THROUGH REAL OBJECT - Jais, Perminus; Salam, Urai; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was intended to improve the students? ability in describing things through real object. The aspects of speaking skill focused in this research were accuracy and fluency. The research method was a classroom action research. The subject of this research was Grade VIII B at junior high school SMP Negeri 3 Sepaukat Sintang regency which consists of 28 students. The data was collected by using oral test, observation checklist and field note, It was analyzed by describing oral test, observation checklist and field note, and by using formula of mean score. The findings indicated the students? ability in describing things improved by using real object as a media in two cycles. The students? mean score in the first cycle was 59.82, the second cycle was 74.11.Describing things through real object is an interesting strategy that can be applied in the classroom. It helps the researcher to remind the student about the things to be described. So, it is hoped that they can speak more fluently. Moreover, by holding something on their hand, the students feel easier to do describing in the front of the class. In addition, the students could learn many vocabularies and grammar through describing things.